Age of onset of disease in subjects with severe periodontitis: A 9‐ to 34‐year retrospective study - Thorbert‐Mros, Sara; Cassel, Björn; Berglundh, Tord (Journal of clinical periodontology, 2017)
Aim The aim was to retrospectively assess the age of onset of disease in a group of patients, 30‐45 years of age, diagnosed with severe, generalised periodontitis. Material & methods Seventy‐four patients agreed to be part of the study. Patient files and radiographs of 42 patients were retrieved from >80 private and public dental clinics. Interproximal sites in radiographs presenting with identifiable cement‐enamel junction (CEJ) and alveolar bone crest (BC) were analysed. The distance between CEJ and BC was measured, and two thresholds were used; ≥3 mm and ≥5 mm. The lowest patient age at which a radiographic examination revealed a CEJ‐BC distance of ≥3 mm (F3) and ≥5 mm (F5) at any site was recorded. Similarly, the highest patient age at which a radiographic examination revealed absence of sites with CEJ‐BC ≥3 mm (L0) was assessed. Results Complete sets of radiographs including periods prior to periodontal breakdown (L0) and disease stages F3, F5 and at recruitment were retrieved in 19 patients. Onset of disease, that is, the interval between L0 and F3, occurred on the average between 22.3 and 28.1 years of age and sites exhibiting severe bone loss (F5) were detected at the age of about 32.4 years. Conclusion Severe, generalised periodontitis in 30‐ to 45‐year‐old subjects of the current sample commenced mainly between 22 and 28 years of age.